2016
DOI: 10.1245/s10434-015-5045-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Infectious Complications are Associated with Adverse Oncologic Outcomes in Esophageal Cancer Patients Undergoing Preoperative Chemotherapy

Abstract: The incidence of postoperative infectious complications, in particular pulmonary infection, is associated with unfavorable prognosis in patients with esophageal cancer undergoing preoperative chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 36 publications
2
53
1
Order By: Relevance
“…These results indicate that early diagnosis, prompt treatment, and careful postoperative management are important factors to improve OS and DFS. 24,25 RLN metastasis was frequent in esophageal cancer patients and was associated with poor survival and the removal of RLN lymph nodes could improve OS and DFS in ESCC patients, [26][27][28] which was in accordance with our results. Thus, RLN lymphadenectomy was 29 specialized adjuvant therapy for ESCC needs to be investigated.…”
Section: Quality Of Lifesupporting
confidence: 91%
See 1 more Smart Citation
“…These results indicate that early diagnosis, prompt treatment, and careful postoperative management are important factors to improve OS and DFS. 24,25 RLN metastasis was frequent in esophageal cancer patients and was associated with poor survival and the removal of RLN lymph nodes could improve OS and DFS in ESCC patients, [26][27][28] which was in accordance with our results. Thus, RLN lymphadenectomy was 29 specialized adjuvant therapy for ESCC needs to be investigated.…”
Section: Quality Of Lifesupporting
confidence: 91%
“…Two of three independent prognosis factors were tumor‐related (pTNM stage and tumor length), one was surgeon‐related. These results indicate that early diagnosis, prompt treatment, and careful postoperative management are important factors to improve OS and DFS …”
Section: Discussionmentioning
confidence: 87%
“…Similarly, three independent single institutes in high‐volume centers of Japan have shown that pneumonia has a negative impact on OS after esophagectomy. The incidence of postoperative infectious complications and, in particular, pulmonary infections, is associated with unfavorable prognosis in patients with esophageal cancer undergoing preoperative chemotherapy 1, 2, 33…”
Section: Resultsmentioning
confidence: 99%
“…Albeit recent advancements in surgical techniques and perioperative care, the postoperative morbidity rate is as high as approximately 40% after esophageal cancer surgery,1, 2 and 20–30% after both gastric cancer surgery3, 4, 5 and colorectal surgery 6, 7, 8. Various reports have shown that such postoperative complications frequently reduce the overall survival (OS) as well as cancer‐specific survival after major surgery for cancer 9.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies in cancer patients have confirmed an association between perioperative factors such as hypothermia 37 , blood loss 38,39 , and postoperative infections 40,41 , and increased cancer recurrence and reduced cancer-specific survival following cancer surgery.…”
Section: Introductionmentioning
confidence: 98%